2017
DOI: 10.1213/ane.0000000000002227
|View full text |Cite
|
Sign up to set email alerts
|

Methodological and Reporting Quality of Systematic Reviews Published in the Highest Ranking Journals in the Field of Pain

Abstract: Endorsement of PRISMA in instructions for authors was not a guarantee of compliance. Methodological and reporting quality of pain-related SRs should be improved using relevant checklists. This can be remedied by a joint effort of authors, editors, and peer reviewers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 22 publications
3
27
1
Order By: Relevance
“…Therefore, these may be some common methodological shortcomings of any types of SRs. In SRs, assessing the risk of bias of primary studies and investigating publication bias are of great importance as these will gauge the validity of meta-analytic results, affect the interpretation of results, and limit our ability to draw conclusions [43,44]. Unfortunately, only 28.6% of IPD-NMAs used a satisfactory technique for assessing the RoB in individual studies included, and only 19% of IPD-NMAs assessed the potential impact of RoB on the results of the meta-analyses.…”
Section: Findings and Interpretationsmentioning
confidence: 99%
“…Therefore, these may be some common methodological shortcomings of any types of SRs. In SRs, assessing the risk of bias of primary studies and investigating publication bias are of great importance as these will gauge the validity of meta-analytic results, affect the interpretation of results, and limit our ability to draw conclusions [43,44]. Unfortunately, only 28.6% of IPD-NMAs used a satisfactory technique for assessing the RoB in individual studies included, and only 19% of IPD-NMAs assessed the potential impact of RoB on the results of the meta-analyses.…”
Section: Findings and Interpretationsmentioning
confidence: 99%
“…However, most non-Cochrane reviews only provided a list of included studies. If we rely on inappropriate reasons to exclude studies, it would introduce bias, which would in uence the transparency, validity and reported quality of our results 51,52 . Hence, it was obvious that Cochrane reviews showed better methodological quality than non-Cochrane review 46,47 .…”
Section: Discussionmentioning
confidence: 99%
“…In the methodological study by Thabut et al, journals with a JIF greater than 5 were considered to be high impact. Riado Minguez et al used first quartile journals in the Journal Citation Reports (JCR) for a specific year to determine "high impact" [77]. Ultimately, the definition of high impact will be based on the number of journals the investigators are willing to include, the year of impact and the JIF cut-off [78].…”
Section: Some Frequently Asked Questions About Methodological Studiesmentioning
confidence: 99%